2010
DOI: 10.5223/kjpgn.2010.13.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Intussusception in Children: Spontaneous Resolution vs. Surgical Intervention

Abstract: Purpose: Intussusception is one of the most common causes of an acute abdomen in infancy. The majority of pediatric cases of intussusception are of the ileocolic type and usually idiopathic. Small bowel intussusception is rarely diagnosed in children, and few cases have been reported. The purpose of this study was to determine the clinical features and causes of small bowel intussusception in children. Methods: We retrospectively reviewed the clinical and radiologic findings of 21 children with small bowel int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…We found that most of the intussusceptions were ileocolic, with only 1 small bowel case. Small bowel intussusception is known to be rare, representing about 1.68% to 17% of all intussusceptions [18]. This agrees with our result, which showed only 1 small bowel intussusception (0.7%) among all the cases.…”
Section: Discussionsupporting
confidence: 93%
“…We found that most of the intussusceptions were ileocolic, with only 1 small bowel case. Small bowel intussusception is known to be rare, representing about 1.68% to 17% of all intussusceptions [18]. This agrees with our result, which showed only 1 small bowel intussusception (0.7%) among all the cases.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, given that our patient underwent the surgical intervention only after 2 days of hospitalization, we have to consider the possibility of a missed diagnosis that could have led to strangulation of the small bowel that occurred during that time period. However, spontaneously reduced small bowel intussusception is presented as a benign disease in most patients, and usually is not associated with bowel ischemia or necrosis [9]. As has been noted, Meckel's diverticulum (MD), a vitelline duct remnant, shows no symptoms in most cases but rather causes complications in the patient such as hemorrhage, intestinal obstruction, inflammation, and perforation in less than 5% of cases [1011] Considering its frequency, MD could be thought as a possible cause of SBO in this patient.…”
Section: Discussionmentioning
confidence: 99%